Cholesterol, Glucose and Blood Cells Count of Rabbit Doe Fed Katuk (Sauropus androgynus L. Merr) Leaf Meal as Supplementation - Akbar, M; Sjofjan, O; Minarti, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Abstractl.Â This study was aimed to determine the ability of katuk that can affected cholesterol, glucose, erythrocyte, leukocyte, and thrombocyte during 3 weeks treatment. Twenty four does were raised from 6â12 month old, divided into three blocks, four treatment diets, and two replications. The treatments were P0= control diet, P1= 99% control diet + 1% katuk leaf meal, P2= 98% control diet + 2% katuk leaf meal, and P3= 97% control diet + 3% katuk leaf meal. The variables observed were cholesterol, glucose, erythrocyte, leukocyte, and thrombocyte. Cholesterol and glucode were determined with colorimetri methode with GOD-PAP, erythrocyte, leukocyte, and trombocyte with haemocytometer.Â Data were analyzed using analysis of variance (anova), followed by Duncans Multiple Test Range. The results showed that addition of katuk leaf meal can decreased cholesterol (50.67â48.34 mg/dl) and glucose (119â115 mg/dl) and increased erythrocyte (6.17â6.25x106/mm3) during 3 weeks experiment, whereas leukocyte, and thrombocyte not affected by katuk leaf meal. It is concluded that addition katuk leaf meal can decreased cholesterol and glucose and increased erythrocyte, whereas leukocyte and thrombocyte not affected by katuk leaf meal.Â Key words: Katuk leaf meal, cholesterol, glucose, blood cellÂ Abstrak.Â Penelitian bertujuan untuk mengetahui pengaruh pemberian tepung daun katuk terhadap kadar kolesterol darah, glukosa darah, eritrosit, leukosit, dan trombosit kelinci betina. Dua puluh empat kelinci betina umur 6â12 bulan dibagi kedalam tiga kelompok dengan empat perlakuan pakan masing-masing dua ulangan. Perlakuan pakan yang diberikan adalah P0= pakan kontrol, P1= 99% pakan kontrol + 1% tepung daun katuk, P2= 98% pakan kontrol + 2% tepung daun katuk, dan P3= 97% pakan kontrol + 3% tepung daun katuk. Variabel yang diamati adalah kolesterol darah, glukosa darah, eritrosit, leukosit dan trombosit setelah 3 minggu perlakuan. Kadar kolesterol dan glukosa diukur dengan metode kolorimetri menggunakan GOD-PAP, jumlah eritrosit, leukosit, dan trombosit dengan haemocytometer. Data yang diperoleh dianalisis menggunakan analisis variansi, dilanjutkan dengan Uji Jarak Berganda Duncanâs. Hasil penelitian menunjukkan bahwa penambahan daun katuk dapat menurunkan kadar kolesterol (50,67â48,34 mg/dl) dan glukosa darah kelinci betina (119-115 mg/dl) dan meningkatkan eritrositÂ (5,93â6,25x106/mm3). Sedangkan leukosit dan trombosit tidak terpengaruh oleh penambahan tepung daun katuk. Kesimpulan penelitian adalah penambahan tepung daun katuk pada pakan dapat menurunkan kadar kolesterol dan glukosa darah kelinci betina, dan meningkatkan jumlah eritrosit tetapi tidak mempengaruhi jumlah leukosit dan trombosit.Â Kata kunci: Tepung daun katuk, kolesterol, glukosa, sel darah